2007
DOI: 10.3748/wjg.v13.i13.1980
|View full text |Cite
|
Sign up to set email alerts
|

Recto-vestibular disruption defect resulted from the malpractice in the treatment of the acquired recto-vestibular fistula in infants

Abstract: AIM:To explore the pathogenesis of the rectovestibular disruption (RVD) defect and to recommend a successful repair, and prevention of it. METHODS:Clinical records of 15 girls, age ranged from 3 to 15 (median, 7.5) years, with acquired rectovestibular fistula (RVF) mistreated before were retrospectively reviewed. All of them presented an abnormal appearance of perineum and were suffering from some degree of fecal incontinence, and those were graded Ⅲ to Ⅳ by Li Zheng's Score. Repair of anal sphincters and reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Other investigators believe that it is an acquired condition [9][10][11][12]. Sun et al [13] compared the histologic findings in a group of 19 patients with fistula and a normal anus to another group of 10 having a fistula associated with imperforate anus and suggested that most RVFNA originated from a vulvar abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators believe that it is an acquired condition [9][10][11][12]. Sun et al [13] compared the histologic findings in a group of 19 patients with fistula and a normal anus to another group of 10 having a fistula associated with imperforate anus and suggested that most RVFNA originated from a vulvar abscess.…”
Section: Discussionmentioning
confidence: 99%
“…This condition does not interfere with development and growth, and daily life inconvenience is also rare. Therefore the main reason for surgery is often psychological, which leads to high expectations from patients and parents for the surgery [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, no matter which approach is used, fistulotomy or seton therapy must never be considered, because they can cause severe a rectovestibular disruption defect [5] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Also, earlier authors reported rectovestibular disruption following the repair of acquired rectogenital fistula. 9 We placed a 2cm transverse incision between the anus and vagina which was carefully dissected until the fistula was identified and excised. The rectal and vaginal defects were repaired in two layers and the wound closed in layers by careful tissues apposition.…”
Section: Discussionmentioning
confidence: 99%